High barrier properties against sulfur mustard of graphene oxide/butyl rubber composites. (20th January 2019) - Zheng, Long; Wang, Deyin; Xu, Zongchao; Zhang, Liqun; Liu, Li; Wen, Shipeng
Abstract: Protection against sulfur mustard (HD) is essential for the safety of the operators in the lab and in war. In this research, graphene oxide/butyl rubber (GO/IIR) composites were first prepared by a green method of latex compounding. This method achieved uniform dispersion of GO in IIR matrix for the GO content up to 2 phr (parts per hundreds of rubber). More importantly, there was a strong interfacial interaction between GO and IIR chains. When the GO content was 2 phr, the tear and tensile strengths of the GO/IIR composites were increased by 44% and 102%, respectively, compared with those of pure IIR. Additionally, it was found that the protective barrier properties against HD of GO/IIR composites increased with the increase in the GO content. When the GO content was 3 phr, a shielding filler network was formed by GO in the IIR matrix, and the diffusion coefficient of HD in IIR was decreased by 46%. The research results are of substantial importance for protection against HD and against more toxic gases or liquids.